Effect of Soot Particle Diameter to Soot Movement in Diesel Engine - Mohd Hafidzal, Mohd Hanafi; Mohamad Shukri , Zakaria; Muhammad Zaidan, Abdul Manaf; Mohd Noor Asril, Saadun (MTUN UTeM, 2013)
Soot is one of the end product produced from the combustion of diesel engine. It can adversely affect the performance of the engine. It can cause the lubricant oil to be dirty thus increase its viscosity. These will results to frequent change of lubricant oil. Therefore, the focus of this study is related to the mechanism soot particles movement during the combustion process in the cylinder of diesel engine. The study of the path movement of soot particles from the initial position where it was formed to the last position was carried out. To analyze their movements, the data formation of soot particles was obtained through the simulation of combustion engine using Kiva-3V software which was used in previous investigation. The data that were obtained from the Kiva-3v simulation were velocity vectors of the soot, fuel, temperature, pressure and others. This data is used in the MATLAB routine to calculate the location of soot particles in the combustion chamber. Mathematics algorithm which is used in the MATLAB routine is trilinear interpolation and 4th order of Runge Kutta. In this study, the influence of soot particles diameter with different angular (θ) is included in the calculation to determine its movement. Results from this study shows that if the size of soot particles is bigger, the probability of the movement of soot particles to the combustion chamber wall is high thus contaminating the lubricant oil.